The Effect of Financial Literacy, Online Taxation, and the E-Wallet PayLater Online Payment System on Impulsive Buying Behavior in Online Shopping - Herlin Maulidiana; Hendrik Suhendri; Ahmad Mukoffi (International Research & Development for Human Beings (IRDH), 2026)
Digital payment systems make transactions easier by eliminating the need for cash, allowing payments to be completed more quickly and conveniently. This study aims to analyze the influence of financial literacy, online tax imposition, and digital payment systems (e-wallet and paylater) on impulsive buying behavior in online shopping. This study uses a quantitative approach with a survey method on students of Tribhuwana Tunggadewi University Malang. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that financial literacy has a negative effect on impulsive buying behavior. Conversely, online tax imposition and e-wallet and paylater digital payment systems have a positive effect on impulsive buying behavior. Simultaneously, all variables have a significant effect on impulsive buying. This study confirms that financial literacy is important in controlling consumptive behavior, while the convenience of digital payment systems can encourage impulsive buying in the digital era.